Identification of angiotensin II-responsive circadian clock gene expression in adrenal zona glomerulosa cells and human adrenocortical H295R cells - Otani, Tomohiro; Miyake, Takahito; Ota, Takumi; Yarimizu, Daisuke; Nakagawa, Yuuki; Murai, Iori; Okamura, Hitoshi; Hasegawa, Emi; Doi, Masao (Frontiers in Endocrinology, 2025)
The mammalian circadian timing system is organized in a hierarchy, with the master clock residing in the suprachiasmatic nucleus (SCN) of the hypothalamus and subsidiary peripheral clocks in peripheral tissues. Because of the diversity of peripheral tissues and cell-types in the body, the existence of autonomous clock and identification of its potential entrainment signals need to be empirically defined on a cell type-by-cell type basis. In this study, we characterized the basic circadian clock properties of the adrenal zona glomerulosa cells, or ZG cells. Using isolated adrenal explants from Per2Luc mice, dissociated ZG cells from Per2-dluc rats, and a related human adrenocortical cell line H295R, we showed that ZG cells possess genetically-encoded, self-sustained and cell-autonomous circadian clock. As to the potential entrainment signals, angiotensin II (Ang II) caused phase-dependent phase-shifts of adrenal ZG cells in cultured slices. Ang II treatment also drove initiation (or reset) of circadian clock gene expression in H295R cells with associated immediate up-regulation of PER1 and E4BP4 mRNA expression. We found that the type I Ang II receptor blocker CV11974, one of the most widely used clinical drugs for hypertensive diseases, caused attenuation of the phase resetting of H295R cells. Our in vitro data provide a basis to understand and argue for the adrenal gland ZG cells as a component of autonomous and entrainable peripheral clocks.